URGENSI PENGATURAN JUSTICE COLLABORATOR DALAM HUKUM PIDANA INDONESIA - Batavia Putri; Evi Deliana; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The position of the witness is very important in a judicial process, because the witness hasinformation based on what he saw and experienced to facilitate the proof of the wrongdoing of the suspectand the defendant. The regulation of Justice Collaborator is something new in Indonesia. JusticeCollaborator is a witness, who is also a perpetrator, but wants to cooperate with law enforcement in orderto dismantle a case and even return the assets resulting from the crime of corruption if the asset is in them.In Indonesia's positive law, the existence of justice collaborator has not yet been given a comprehensivearrangement, so that the existence of Justice Collaborator is responded to differently by law enforcement.The appointment of a suspect as a Justice Collaborator is expected to assist law enforcement in exposinglarger crimes or other perpetrators who should be held responsible. On the other hand, the establishment ofa Justice Collaborator will avoid a suspect or defendant in a corruption case from the most severe criminalthreat. Based on the description, the problem can be formulated as follows: First, how the JusticeCollaborator is regulated in Indonesian criminal law. Second, what is the idea of setting up a JusticeCollaborator in Indonesian criminal law.This type of research can be classified in the type of normative research, namely research oncomparative law. This study uses secondary data sources consisting of primary legal materials, secondarylegal materials and tertiary legal materials, data collection techniques in this study with literature studies.From the results of the research problem there are two main things that can be concluded. First, theregulation in criminal law against Justice Collaborator is spread through several regulations. But from theexisting regulations there is no guarantee of legal certainty against the Justice Collaborator. Secondly, theidea of organizing witnesses for collaborating perpetrators (Justice Collaborator) in criminal law is veryurgent. This urgency is caused because the Criminal Procedure Code (KUHAP) has not yet regulated theJustice Collaborator.Keywords: Justice Collaborator, Corruption, Legal Reform